2017
DOI: 10.5808/gi.2017.15.1.28
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Profiles of Blood Cells Are Distinct between Early-Onset Obese and Control Individuals

Abstract: Obesity is a highly prevalent, chronic disorder that has been increasing in incidence in young patients. Both epigenetic and genetic aberrations may play a role in the pathogenesis of obesity. Therefore, in-depth epigenomic and genomic analyses will advance our understanding of the detailed molecular mechanisms underlying obesity and aid in the selection of potential biomarkers for obesity in youth. Here, we performed microarray-based DNA methylation and gene expression profiling of peripheral white blood cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For example, the offspring of obese mothers presented several CpG sites differentially methylated in cord blood in comparison with offspring from normal weight mothers [87]. Other regions studied, were mainly hypomethylated in obese children and located in the gene body region, and revealed a unique cluster of obese individuals that was differentiated from the normal weight children [88]. In addition, some of these genes are implicated in lipid and glucose metabolism, differential body size and body composition in children [89].…”
Section: Dna Methylation Markers In Obesitymentioning
confidence: 97%
“…For example, the offspring of obese mothers presented several CpG sites differentially methylated in cord blood in comparison with offspring from normal weight mothers [87]. Other regions studied, were mainly hypomethylated in obese children and located in the gene body region, and revealed a unique cluster of obese individuals that was differentiated from the normal weight children [88]. In addition, some of these genes are implicated in lipid and glucose metabolism, differential body size and body composition in children [89].…”
Section: Dna Methylation Markers In Obesitymentioning
confidence: 97%
“…In this regard, epigenetic dysregulation of several genes ( Nna t and Peg3 ) of the Trim28 -imprinted gene network also influences the risk for the offspring of developing obesity, as elegantly described by Dalgaard et al [79]. Additionally, the DNA methylation signature in blood cells is distinct between early-onset obese and control individuals [80]. Moreover, Dick et al [81] described an association between an increased BMI and an increased methylation at the HIF3A locus in blood cells and in adipose tissue of the same subjects, suggesting that DNA methylation perturbation of hypoxia-inducible factor (HIF) signaling might represent a mark of increased body adiposity.…”
Section: Dna Methylation and Future Medicinementioning
confidence: 99%
“…Some cross-sectional studies have reported a significant association between obesity or adiposity status, and DNA methylation [ 24 ]. These studies demonstrate that some regions of different genes studied were hypomethylated in obese children and located in the gene body region, and revealed a unique cluster of obese individuals that was differentiated from the normal-weight children [ 25 ]. Some of these genes are implicated in lipid and glucose metabolism, differential body size, and body composition in children [ 26 ].…”
Section: Discussionmentioning
confidence: 99%